Cultural exchange : Jews, Christians, and art in the medieval marketplace - Shatzmiller, Joseph (Princeton, New Jersey : Princeton University Press, 2013)
Demonstrating that similarities between Jewish and Christian art in the Middle Ages were more than coincidental, Cultural Exchange meticulously combines a wide range of sources to show how Jews and Christians exchanged artistic and material culture. Joseph Shatzmiller focuses on communities in northern Europe, Iberia, and other Mediterranean societies where Jews and Christians coexisted for centuries, and he synthesizes the most current research to describe the daily encounters that enabled both societies to appreciate common artistic values. Detailing the transmission of cult.
pt. 1. Pawnbrokers : agents of cultural transmission -- pt. 2. Human imagery in medieval Ashkenaz -- pt. 3. At the marketplace : professionals in the service of the "other."
Includes bibliographical references and index.
Print version record.
In English.
Master record variable field(s) change: 650
Keywords: Jews -- Europe, Western -- Civilization; Jews -- Europe, Western -- Social life and customs -- To 1500.; Christians -- Europe, Western -- Civilization; Christians -- Europe, Western -- Social life and customs -- To 1500.; Europe, Western -- Civilization -- To 1500.; Europe, Western -- Civilization -- Jewish influences; Europe, Western -- Ethnic relations; BUSINESS & ECONOMICS -- Industries -- Retailing; BUSINESS & ECONOMICS -- Marketing -- Direct; TRAVEL -- Shopping; HISTORY -- Medieval; General European History; History; Recht; Regional History; Electronic books